Expand the following: \begin{align} v= \frac{F_b}{m}t+v0 =&\cssId{Step1}{x(t)=v_td_t}\\[3px] &\cssId{Step2}{x(t)= -\frac{F_b}{m}t+v_0dt}\\[3px] &\cssId{Step3}{x(t)= -\frac{F_b}{2m}t^2+v_0t+C}\\[3px] &\cssId{Step4}{x(t)= -\frac{F_b}{2m}t^2+v_0t}\\[3px] \end{align}

- In the first step we calculate the position equation with the speed, the variable d and the time
- In the second step we change the speed variable to the previously equation of speed
- In the third step we change the variable d to initial speed and the variable C
- In the fourth step we remove the variable C because his value is zero